Professional Web Accessibility Auditing Made Easy - Open Textbook Library (Open Textbook Library, 2018)
Digital accessibility skills are in high demand, as the world becomes more aware of barriers in digital content that prevent some people from participating in a digital society. These are essential skills for web developers, and essential knowledge for organizations that want to ensure their web content is reaching the broadest audience possible.
Introduction -- 1. Aspects of Web Accessibility Auditing -- 2. Introduction to WCAG 2.0 -- 3. Automated Testing Tools -- 4. Manual Testing Strategies -- 5. Assistive Technology Testing -- 6. User Testing -- 7. Web Accessibility Reporting -- 8. Other Accessibility Standards
In English.
Description based on print resource
Keywords: Computer Science -- Textbooks